Daylighting simulation of a heritage building by comparing matrix methods and solar models - Saraiva, Nuno Baía (2021)
Lighting simulation is a useful instrument in predicting lighting conditions in buildings. Modelers can use several matrix methods according to the buildings’ characteristics and the objectives of the analysis. However, it is unknown which methods are the most appropriate for lighting analysis of heritage buildings. The Joanina Library located in the University of Coimbra – a World Heritage building – was used to compare different matrix methods (2PH, 3PH, and 5PH) under several solar models (BRL, DISC, Perez, and Reindl) using Radiance-based simulations. On-site measurements (indoor and outdoor) were used to calculate each method’s accuracy under different solar models. The combination of the 2PH method with the DISC solar model presented the highest accuracy with an average MBEr and RMSEr of 2.8 % and 43.6 %, respectively. Therefore, the 2PH method was the best choice for the case study, even though the 3PH method may also be considered, especially for parametric studies of improving measures.